PEMBUATAN PAVING BLOCK DENGAN BAHAN DASAR SERAT TANDAN KOSONG KELAPA SAWIT - Yehezkiel Sinuraya; Budi Mulyara; Rafael Remit Winardi (Jurnal Agro Fabrica, 2022)
Lack of waste management of oil palm empty fruit bunches and the lack of utilization of oil palm empty fruit bunches (EFB). Based on this, the researcher wants to use empty bunches as paving blocks that meet the quality standards of SNI 03-0691-1996 which include the requirements for appearance, size, compressive strength, and water absorption. This research was conducted for 3 months and the sample to be used was obtained from the Pagar Merbau Palm Oil Mill. Oil palm empty fruit bunches are obtained from the process of soaking with the chemical NaOH for a while so that the fibers do not get moldy. Empty bunches of fiber, water, cement, and sand are mixed and stirred evenly which is then printed on a 21.5 x 11 x 6 cm size mold. The research was conducted at the ITSI campus (Indonesian Palm Oil Technology Institute) Medan and the Civil Engineering Laboratory of the Medan State Polytechnic. This research is experimental. Variable testing using ANOVA test with a confidence level of 95% or with a significance level of 5% (α = 0.05). The results showed that the appearance and size of paving blocks with fiber composition of 0%, 5%, 10%, 15%, and 20% oil palm empty fruit bunches met the requirements according to SNI 03-1091-1996. There is a relationship between the weight of paving blocks and the fiber composition of 0%, 5%, 10%, 15%, and 20% of the compressive strength of paving blocks and there is no relationship between the weight of paving blocks and the fiber composition of 0%, 5%. , 10%, 15%, and 20% of the water absorption of paving blocks.